2011
DOI: 10.1186/cc10534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review: Humidifiers during non-invasive ventilation - key topics and practical implications

Abstract: Inadequate gas conditioning during non-invasive ventilation (NIV) can impair the anatomy and function of nasal mucosa. The resulting symptoms may have a negative effect on patients' adherence to ventilatory treatment, especially for chronic use. Several parameters, mostly technical aspects of NIV, contribute to inefficient gas conditioning. Factors affecting airway humidity during NIV include inspiratory flow, inspiratory oxygen fraction, leaks, type of ventilator, interface used to deliver NIV, temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 31 publications
0
41
0
1
Order By: Relevance
“…Although there is a lack of firm recommendations on the optimal conditioning of gas delivered at the airway opening during noninvasive respiratory support in newborn infants, adult studies seem to suggest that an absolute humidity between 15 and 30 mg H 2 O/L should be targeted . Studies have shown that an absolute humidity of less than 10 mg H 2 O/L has been associated with a dry upper airway during nasal CPAP and dryness related symptoms started to appear when absolute humidity was lower than 15 mg H 2 O/L . Dry gases (5 mg H 2 O/L) were less tolerated than humidified gases and comfort scores were half of those with humidification .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a lack of firm recommendations on the optimal conditioning of gas delivered at the airway opening during noninvasive respiratory support in newborn infants, adult studies seem to suggest that an absolute humidity between 15 and 30 mg H 2 O/L should be targeted . Studies have shown that an absolute humidity of less than 10 mg H 2 O/L has been associated with a dry upper airway during nasal CPAP and dryness related symptoms started to appear when absolute humidity was lower than 15 mg H 2 O/L . Dry gases (5 mg H 2 O/L) were less tolerated than humidified gases and comfort scores were half of those with humidification .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore assumed that the contribution of the humidifier in conditioning the gas should be less during noninvasive respiratory support. Although data in the neonatal population are lacking, studies in adults suggest that an absolute humidity of 15–30 mg H 2 O/L might be optimal . For this reason, manufacturers have added a noninvasive mode to their humidifiers, which uses different humidification settings than the traditionally used invasive mode.…”
Section: Introductionmentioning
confidence: 99%
“…The sample was small, involving healthy participants, and the results would probably be different in situations in which other risk factors (age, nutritional status, medication use, presence of comorbidities, and level of consciousness) were present 12 21 , 23 Another important limitation was the lack of a control group receiving heated humidification 24 25 …”
Section: Discussionmentioning
confidence: 99%
“…Assessment of patients' need for humidification was done less often by respondents in this survey. Patients who receive supplemental oxygen via non-invasive ventilation or through invasive ventilation via an artificial airway require adequate humidification to prevent secretions from becoming too viscous, forming mucus plugs in distal airways and resulting in lung volume loss or infection; [16,18] therefore, humidification therapy and regular assessment for changes in patient humidification needs should form part of daily practice in the ICU. Oscillatory positive expiratory pressure (PEP) in the form of a blow bottle seems to be a popular treatment intervention for physiotherapists in SA, as a large number of respondents in the current and 2005 [6] surveys reported using it as a treatment strategy.…”
Section: Resultsmentioning
confidence: 99%